Human cervical cancer oncogene-1 over expression in colon cancer and its clinical significance - Meng, Kai (Int J Clin Exp Med, 2015)
Objective: This study was to explore the expression of human cervical cancer oncogene-1 (HCCR-1) in colon cancer and its clinical significance. Methods: RT-PCR, immunohistochemistry and Western blot assay were employed to detect HCCR-1 expression in 152 colon cancers, 43 adjacent non-cancerous tissues and 37 normal tissues. In addition, immunohistochemistry was done to detect CEA in colon cancers. Results: The mRNA expression of HCCR-1 in colon cancers was higher than that in the adjacent non-cancerous tissues (P < 0.05), and the mRNA expression of HCCR-1 in adjacent non-cancerous tissues was higher than that in normal tissues (P < 0.05). The positive rate of HCCR-1 in colon cancers was 80.9%, which was higher than that in adjacent non-cancerous tissues (P < 0.05). Almost no HCCR-1 expression was observed in normal tissues, weak expression in adjacent non-cancerous tissues and strong expression in colon cancers. The positive rate of HCCR-1 in colon cancer at Duke stage B-C was 87.3%, which was higher than that in stage A colon cancer (63.6%, P < 0.05). Conclusion: HCCR-1 is over-expressed in colon cancers, indicating that HCCR-1 may participate in occurrence and development of colon cancer and has a correlation with the pathological progress of colon cancer progression.